Analysis of Learning Resource Utilization by Students of the Educational Technology Study Program, FIP UNP - Putri, Lidya Indah; Yeni J, Fetri; Novrianti, Novrianti; Rahmi, Ulfia (The Future of Education Journal, 2025)
Higher education today faces various challenges and opportunities influenced by the development of technology and information. In this context, the utilization of learning resources becomes an important aspect to enhance the quality of education and support the completion of students' assignments. Students are expected to be able to utilize various learning resources such as e-journals, textbooks, e-books, as well as artificial intelligence-based tools like ChatGPT and Perplexity to support the completion of their coursework. This research aims to analyze the utilization of learning resources by students in completing their coursework. The type of research used is descriptive quantitative research to describe the actual situation based on data obtained from a predetermined sample. The sample in this study consisted of 105 students selected using the proportionate stratified random sampling technique. Based on the data analysis results, the average percentage of resource utilization is as follows: e-journal 81.79% (very good category), textbooks 74.57% (good category), e-books 79% (good category), ChatGPT 83.67% (very good category), and Perplexity 82.1% (very good category). These findings indicate that students predominantly use digital resources that are considered practical, relevant, and efficient in completing their coursework. Although textbooks are still used, their usage is the lowest compared to other digital sources. Overall, the utilization of learning resources by students of the Educational Technology Study Program at FIP UNP has been effective, but improving information literacy is essential so that students can be more discerning in choosing credible sources that meet their academic needs.